2020
DOI: 10.1080/09537104.2020.1817361
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and renal failure in the SARS-CoV-2 syndrome

Abstract: The coronavirus disease 19 (COVID-19) is a highly transmittable viral infection caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 utilizes metallocarboxyl peptidase angiotensin receptor (ACE) 2 to gain entry into human cells. Activation of several proteases facilitates the interaction of viral spike proteins (S1) and ACE2 receptor. This leads to cleavage of host ACE2 receptors. ACE2 activity counterbalances the angiotensin II effect, its loss may lead to elevated angiotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 44 publications
(77 reference statements)
1
19
0
2
Order By: Relevance
“… [54] 81 M: 60 49 USA This study found increased IPF (greater than7) in COVID-19-infected subjects who had evidence of elevated D-dimers and AKI. [53] Increased P-selectin level Non-severe: 20 Severe: 34 M: 69 M: 59 65 62 Ireland Circulating levels of soluble P-selectin increased in COVID-19 patients compared to the control cohorts and intriguingly, could differentiate between non-severe and severe COVID-19 cohorts. [5] Non-severe: 71 Severe: 44 M: 48 M: 64 54.92 59 Canada Platelet activation, assessed by surface expression of P-selectin and CD63, was evident in patients with severe COVID-19 and strongly correlated with levels of D-dimers.…”
Section: Prognostic Factors Associated With Platelets In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“… [54] 81 M: 60 49 USA This study found increased IPF (greater than7) in COVID-19-infected subjects who had evidence of elevated D-dimers and AKI. [53] Increased P-selectin level Non-severe: 20 Severe: 34 M: 69 M: 59 65 62 Ireland Circulating levels of soluble P-selectin increased in COVID-19 patients compared to the control cohorts and intriguingly, could differentiate between non-severe and severe COVID-19 cohorts. [5] Non-severe: 71 Severe: 44 M: 48 M: 64 54.92 59 Canada Platelet activation, assessed by surface expression of P-selectin and CD63, was evident in patients with severe COVID-19 and strongly correlated with levels of D-dimers.…”
Section: Prognostic Factors Associated With Platelets In Covid-19mentioning
confidence: 99%
“… [52] 81 M: 60 49 USA There was a significant correlation between D-dimer levels and MVP; but a negative correlation between MPV and GFR in critically ill cohort. [53] IPF 47 M: 56 59.6 Israel Patients with COVID-19 have increased IPF compared to stable patients with cardiovascular risk factors, suggesting that the enhanced platelet turnover may have a role in the development of thrombotic events in COVID-19 patients. [27] 982 M: 71 68 Europa IPF tended to increase with disease severity.…”
Section: Prognostic Factors Associated With Platelets In Covid-19mentioning
confidence: 99%
“…SARS-CoV-2 has furthermore been shown to bind to platelets via ACE2, leading to platelet activation and immunothrombosis 64 66 . Thus, platelet activation may represent a potential player in the pathophysiology of COVID-19 AKI 67 , 68 . Circulating prothrombotic autoantibodies that target phospholipids and phospholipid-binding proteins have also been reported 69 .…”
Section: Pathophysiology Of Covid-19 Akimentioning
confidence: 99%
“…A total number of 18 studies were finally included in our analysis, with 3,433 COVID-19 patients, 780 (22.7%) with severe illness (►Table 1). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] All except two were crosssectional studies, with the majority from China (7; 39%), and used heterogeneous combination of clinical endpoints for defining severity of COVID-19 (44% included respiratory failure and/or intensive care unit admission, 33% death, and 6% acute kidney failure or thrombosis; ►Table 1).…”
mentioning
confidence: 99%